Magnetization Transfer Contrast of Various Regions of the Brain in Liver Cirrhosis - Iwasa, Motoh; Kinosada, Yasutomi; Nakatsuka, Atsuhiro; Watanabe, Shozo; Adachi, Yukihiko (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: T1-weighted MR images show high signal intensity in the pallidum of many patients with liver cirrhosis. The purpose of this study was to evaluate quantitative changes in MR signals in patients with liver cirrhosis by using the magnetization transfer technique.METHODS: Magnetization transfer ratios were measured in seven different regions of the brain in 37 patients with liver cirrhosis and in 37 healthy volunteers.RESULTS: The magnetization transfer ratios in patients with liver cirrhosis were significantly lower than those in control subjects in the globus pallidus, putamen, thalamus, corona radiata, and subcortical white matter.CONCLUSION: Abnormal magnetization transfer ratios may be found in otherwise normal-appearing cerebral regions.